ANALYSIS AND DESIGN OF WEB-BASED POSYANDU INFORMATION SYSTEM (CASE STUDY: POSYANDU MANDALA 2) - Fitriyah Kamilah (Jurnal Sistem Informasi dan E-Bisnis, 2021)
In the implementation of the Posyandu, posyandu cadres have recorded and implemented immediately after the posyandu activities were carried out. Recording is done manually by using a standard format that is in accordance with the Posyandu Information System (SIP). The implementation of this manual provides some data that are not valid, delays in processing data and making performance reports on posyandu activity reports, both by posyandu which also involves relevant agencies, Puskesmas and Kelurahan. To overcome this problem, design a posyandu information system using the waterfall system development method and analysis method using the PIECES method. The purpose of this research is to develop a system that is still manual so that it becomes a web-based posyandu information system that can facilitate the processing, searching, and reporting of data on Mandala Posyandu activities 2. The results of this study are to produce a system that can be used by posyandu cadres to help find parents in seeing the growth and development of the ball easier. The analysis and design made can facilitate the delivery of information to posyandu participants and posyandu cadres. Suggestions for developing system design into web-based applications using the programming language PHP and MySQL.Keywords— Posyandu, Information Systems, Toddlers, PIECES.